A regressed germ cell tumor discovered secondary to azoospermia. Issue 2 (8th November 2022) - Tsujioka, Hiroki; Uemura, Keiichiro; Iwahata, Toshiyuki; Inoue, Yasuyuki; Inoue, Minoru; Osaka, Akiyoshi; Nakayama, Akinori; Okada, Hiroshi; Saito, Kazutaka
Abstract : Introduction: Regressed germ cell tumors are a rare disease commonly diagnosed with metastatic symptoms without local symptoms in the testis. Case presentation: A 33‐year‐old man with azoospermia was referred to our hospital. His right testis was slightly swollen, and ultrasonography revealed hypoechogenicity of the right testis with decreased blood flow. Right high orchiectomy was performed. Pathologically, the seminiferous tubules were absent or highly atrophied with vitrification degeneration; however, no neoplastic lesion was confirmed. One‐month post‐surgery, the patient noticed a mass in the left supraclavicular fossa, of which a biopsy revealed seminoma. The patient was diagnosed with a regressed germ cell tumor and underwent systemic chemotherapy. Conclusion: We reported the first case of a regressed germ cell tumor discovered due to complaints of azoospermia.